Design Digital to Analog Control Equipment Using Computer - Jarot Prianggono; Radite PAS (PERTETA, 2002)
This study aim to identify and to analyze the behaviour ouput signal from Digital To Analog Converter (DAC) thet combined with motor DC driver. But before the analysis, the design must be conducted. Typical motor can turn clockwise and counter clockwise. Behaviour of servo motor controller was linear, so the sistem can be named by linear motor controller. This study can we used for the research on the mechatronics field, especially on the agricultural engineering.